Neo-Indian cinema : a breakaway from the conventional Bombay cinema. - Rinita Nadavan. (2010)
For decades, viewers have been fascinated by Bollywood and its conventions which do not quite reflect the real Mumbai society. Due to the increased influence of globalization and the changing Mumbai society, lately, several films extend from Bombay cinema which attempt to subvert the conventions and clichés of Bollywood. I regard these films as “Neo-Indian Cinema” and discuss them in parallel with Bollywood. Neo-Indian Cinema has its own unique attributes which capture the elements of reality prevailing in Bombay society. This essay explores the necessity of the emergence of Neo-Indian Cinema, the different styles adopted by the filmmakers of these films, some of the current major challenges that Neo-Indian Cinema faces and what it can provide for Bombay cinema and eventually the Indian cinema in the long run.